2002
DOI: 10.1016/s0014-5793(02)03040-5
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes enriched for stem cells are protected from anoikis via an integrin signaling pathway in a Bcl‐2 dependent manner

Abstract: Because inhibition of integrin signaling induces apoptosis, we investigated whether keratinocytes expressing L L1 and K K6L L4 integrins (enriched for stem cells) are protected from cell death. Keratinocytes rapidly adhering to type IV collagen expressed highest levels of L L1 and K K6L L4 and of the anti-apoptotic stem cell marker p63. Apoptotic cells were signi¢cantly higher in slowly adhering than in rapidly adhering keratinocytes. Anti-L L1 integrin caused a signi¢cant increase in apoptotic cells, while it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 45 publications
7
95
0
1
Order By: Relevance
“…This gene has been reported to prolong the survival of cells by specifically inhibiting apoptosis [46] . Moreover, the Bcl-2 protein plays an important role in preserving stem cells [47]. In the current work, bone sections of the MTX group (Group C) showed strong positive staining for the anti-apoptotic Bcl2 protein that is supposed to be increased in case of bone injury to protect the mesenchymal cells responsible for bone formation in the bone marrow by inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 52%
“…This gene has been reported to prolong the survival of cells by specifically inhibiting apoptosis [46] . Moreover, the Bcl-2 protein plays an important role in preserving stem cells [47]. In the current work, bone sections of the MTX group (Group C) showed strong positive staining for the anti-apoptotic Bcl2 protein that is supposed to be increased in case of bone injury to protect the mesenchymal cells responsible for bone formation in the bone marrow by inhibiting apoptosis.…”
Section: Discussionmentioning
confidence: 52%
“…The Bcl-2 protein suppresses apoptosis (19) and is present in many long-lived cells (42). Bcl-2 protects hematopoietic and keratinocyte stem cells from apoptotic death (21,43), and over-expression of Bcl-2 increases the numbers of hematopoietic stem cells in vivo (20) and protects hematopoietic stem cells from the harmful effects of a number of chemotherapeutic agents, thus ensuring their survival (44). The expression of Bcl-2 by the prostate stem cell population that has high levels of Sca-1 and significant in vivo proliferative potential is therefore likely to ensure the long-term survival of this cell population.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that cells with stem cell features (quiescence and high proliferative potential) are concentrated in the proximal region of prostatic ducts (9). By using FACS analysis, we determined whether the expression of three antigens, Sca-1, ␣6 integrin, and Bcl-2, known to be expressed by stem cells of other origins (10)(11)(12)(13)(14)(15)(16)(17)(18)(20)(21)(22), differs between the proximal and remaining ductal regions.…”
Section: Cells In the Proximal Region Of Murine Prostatic Ducts Coexpmentioning
confidence: 99%
See 1 more Smart Citation
“…The initiating event of anoikis is not clearly defined. In some cell models Bcl-2 or Bcl-xl can inhibit detachment-induced apoptosis or anokois, suggesting a mitochondria-dependent mechanism (Rytomaa et al, 1999;Coll et al, 2002;Tiberio et al, 2002). Another recent mechanism associated with aniokis is the release of the Bcl-2 family member Bmf from cytoskeletal elements (Puthalakath et al, 2001).…”
Section: Adhesion-mediated Effects On Apoptosismentioning
confidence: 99%